1985
DOI: 10.4319/lo.1985.30.6.1208
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylsulfide in the water column and the sediment porewaters of the Peru upwelling area1

Abstract: The concentration of dimethylsulfide (DMS) and supporting parameters were determined on longshore and cross-shelf traverses in the Peru upwelling area. Vertical DMS profiles were measured at several stations in the marine water column and in the sedimentary porewaters. The distribution of DMS in surface waters is related to the patchiness of the upwelling process and of the resulting phytoplankton biomass. Substantial concentrations of DMS were found in the sedimentary porewaters, with a sharp maximum a few ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 16 publications
7
31
0
Order By: Relevance
“…In addition, sediment also acted as a source of DMS at the bottom. Previous research showed that the bottom sediments contained much higher concentration of DMS in the porewater than in the overlying water column, presumably derived from detritus settled onto the bottom (Andreae, 1985). In the upper ocean, a subtle interplay of biological, chemical and physical factors determines the seawater concentration of DMS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sediment also acted as a source of DMS at the bottom. Previous research showed that the bottom sediments contained much higher concentration of DMS in the porewater than in the overlying water column, presumably derived from detritus settled onto the bottom (Andreae, 1985). In the upper ocean, a subtle interplay of biological, chemical and physical factors determines the seawater concentration of DMS.…”
Section: Introductionmentioning
confidence: 99%
“…The expectation that a shallow MLD will cause high DMS concentrations was the source of the overestimations of DMS by all of the algorithms that used MLD, and not AN01. The Kettle databases also have high DMS concentrations at these most easterly locations, likely due to the very high inshore concentrations measured by Andreae (1985). As the uncertainty in DMS predictive algorithms is still substantial and as studies in different locations, times, or scales often do not agree, caution must be used when such algorithms are used to predict changes in flux of DMS to the atmosphere in future climate scenarios.…”
Section: Mldmentioning
confidence: 99%
“…Hind et al: The use of algorithms to predict surface seawater dimethyl sulphide concentrations during a POC, or were associated with a front that enhanced nutrient availability, or affected the depth of the mixed layer, all leading to enhanced biological production or release of DMS in the environment (Stefels et al, 2007). Much higher DMS concentrations, exceeding 40 nM, have been reported in the coastal waters of the Peruvian upwelling, with the maxima observed within 10 km of the shore, accompanied by elevated levels of phytoplankton biomass (Andreae, 1985).…”
Section: Clouds In the Se Pacific And Dmsmentioning
confidence: 99%
“…Despite the fact that coastal upwelling areas have been identified as hot spots of DMS production, only a few descriptive studies about DMS from these areas have been published: DMS and DMSP have been measured in the Peruvian upwelling (Andreae, 1985;Riseman and DiTullio, 2004), off Oman (Hatton et al, 1999), off West India (Shenoy and Dileep Kumar, 2007) and in the NW African upwelling off Morocco (Belviso et al, 2003) as well as off Mauritania (Franklin et al, 2009). The parameters which influence the temporal development and spatial distribution of DMS as well as DMSP in coastal upwelling areas are not completely understood.…”
Section: Introductionmentioning
confidence: 99%